Profiling public transport users through perceptions about public transport providers and satisfaction with the public transport service - Vicente, P.; Reis, E. (Public Transport, 2016)
Priority has been given to increasing public transport use in the mobility programmes of developed countries as part of a global strategy to manage traffic congestion and air pollution in urban areas. Understanding citizens’ travelling behaviour, their perceptions and satisfaction after experiencing public transport services is crucial to the delineation of efficient future mobility programmes. In this paper we apply cluster analysis to segment public transport users in a Portuguese urban area according to their perceptions of public transport operators and satisfaction with the public transport service. The outcomes reveal four segments of public transport users: one positive, one indifferent and the other two negative. Managerial implications of the findings are discussed.